Prevention of Viral Hepatitis and HIV Infection among People Who Inject Drugs: A Systematic Review and Meta-Analysis - Yen-Ju Chen; Yu-Chen Lin; Meng-Tien Wu; Jenn-Yuan Kuo; Chun-Hsiang Wang (Viruses, 2024)
This study aimed to explore the current evidence on preventing blood-borne virus infections among people who inject drugs (PWID). We conducted a comprehensive search across three databases (PubMed, Embase, Cochrane Library) for relevant articles published in English between 2014 and 2023. We followed the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) guidelines, assessed the quality of the paper using the revised Cochrane Risk of Bias Tool (ROB 2), and conducted a meta-analysis using RevMan 5.3. Completing the harm reduction program (HRP) participation and receiving all three vaccine doses resulted in a 28% reduction in the risk of HBV infection (OR: 0.72, 95% CI: 0.37–1.42). Various interventions increased the willingness of PWIDs to undergo HCV treatment (OR: 5.91, 95% CI: 2.46–14.24) and promoted treatment adherence (OR: 15.04, 95% CI: 2.80–80.61). Taking PrEP, participating in HRP, and modifying risky behaviors were associated with a 33% reduction in the risk of HIV infection (OR: 0.67, 95% CI: 0.61–0.74). Conducting referrals, providing counseling, and implementing antiretroviral therapy resulted in a 44% reduction in the risk of viral transmission (OR: 0.56, 95% CI: 0.47–0.66). Co-infection may potentially compromise effectiveness, so it is important to consider drug resistance.